Impact of simulated rainfall on atrazine wash off from roller crimped and standing cereal rye (Secale cereale L.) residue onto the soil - Maia, Lucas O. R.; Armstrong, Shalamar D.; Kladivko, Eileen J.; Young, Bryan G.; Johnson, William G. (Frontiers in Agronomy, 2025)
The combination of soil residual herbicides and cover crops is an integral part of best management practices for herbicide-resistant weeds. However, the interception of soil residual herbicides by cover crop biomass interferes with herbicides reaching the soil, which can lead to lower weed control efficacy and increased selection pressure for herbicide resistance. Once intercepted, these herbicides can only move to the soil with water from rainfall or irrigation. Field trials were conducted in 2022 and 2023 to investigate the effect of cover crop termination strategies (fallow, standing, and roller crimped) and simulated rainfall volumes (0, 4.2, and 8.3 mm simulated over 20 min; equivalent to 0, 12.5, and 25 mm h-1) on atrazine wash off from cereal rye (Secale cereale L.) biomass onto the soil. The use of roller crimper resulted in an average of 10% greater ground cover relative to the standing cereal rye. Atrazine interception that was bound to rye biomass reached 29 and 94% in 2022 and 2023, respectively. In 2022, the concentration of atrazine in the soil under roller crimped cereal rye was 9% greater than that understanding cereal rye, after 4.2 mm of rainfall. In 2023, when cereal rye biomass more than doubled, only 6% of the applied atrazine was found under roller crimped cereal rye, after 8.3 mm of rainfall. Cereal rye biomass accumulation negatively impacted the amount of atrazine reaching the soil at the time of application. Although the roller crimped cereal rye reduced the amount of herbicide reaching the soil relative to the standing cereal rye, it also reduced atrazine leaching below the 0–5 cm of soil. In cover cropping systems with high levels of cereal rye biomass (e.g., > 7,000 kg ha-1), more than 8.3 mm of rain are required to wash most of the atrazine off of the biomass.